2020
DOI: 10.1142/s2047684120500165
|View full text |Cite
|
Sign up to set email alerts
|

Study the effects of factors on the structure and phase transition of bulk Ag by molecular dynamics method

Abstract: This paper studies the effect of atoms number [Formula: see text] of bulk Ag: [Formula: see text] atoms (Ag[Formula: see text]), 4000 atoms (Ag[Formula: see text]), 5324 atoms (Ag[Formula: see text], 6912 atoms (Ag[Formula: see text] at temperature [Formula: see text][Formula: see text]K, 400[Formula: see text]K, 500[Formula: see text]K, 600[Formula: see text]K, 700[Formula: see text]K, 800[Formula: see text]K, 900[Formula: see text]K, 1000[Formula: see text]K on bulk Ag[Formula: see text] and annealing time [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…OU equal-length non-coding RNA MALAT1 promotes the development of gestational hypertension by regulating the miR-150 ‐5p/ET‐1 axis to enhance oxidative stress and inflammation [ 8 ]. Low vitamin D intake should be considered as a possible risk factor for PIH [ 9 ]. Li et al conducted a nested case-control study to examine the relationship between circulating SFA and risk of PIH [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…OU equal-length non-coding RNA MALAT1 promotes the development of gestational hypertension by regulating the miR-150 ‐5p/ET‐1 axis to enhance oxidative stress and inflammation [ 8 ]. Low vitamin D intake should be considered as a possible risk factor for PIH [ 9 ]. Li et al conducted a nested case-control study to examine the relationship between circulating SFA and risk of PIH [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, metals, alloys in general and low carbon steel (LCS) in particular, are the most common material widely used in all areas of economic and social life. Metals such as Ni, 1 , 2 Fe, 3 5 Al, 6 , 7 and Ag; 8 alloys such as FeCoNi, 9 CuAu, 10 Fe 2 O 3 , 11 AgAu, 12 FeC, 13 AlNi, 14 AuCu, 15 NiCu, 16 18 and NiFe; 19 , 20 nonmetallic polymers; 21 , 22 and polymer–metals 23 have good properties such as durability, fire protection, and good electrical conductivity. When metal or nonmetallic dopants are introduced into polymers, their conductivity increases.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, metals, alloys in general and low carbon steel (LCS) in particular, are the most common material widely used in all areas of economic and social life. Metals such as Ni, , Fe, Al, , and Ag; alloys such as FeCoNi, CuAu, Fe 2 O 3 , AgAu, FeC, AlNi, AuCu, NiCu, and NiFe; , nonmetallic polymers; , and polymer–metals have good properties such as durability, fire protection, and good electrical conductivity. When metal or nonmetallic dopants are introduced into polymers, their conductivity increases. Their highest disadvantage is that they can oxidize or corrode when they are exposed to the environment as microbial corrosion in petroleum and industrial wastewater, , the biodegradation of hydrocarbons, and the methanol extract from marine algae inhibit the corrosion ability of steel in sodium chloride medium .…”
Section: Introductionmentioning
confidence: 99%
“…The other five-membered ring molecules and ionization energies (IEs) and the heats of formation of thiophene were calculated and reached a high precision level of ab initio predictions [ 46 ]. Recently, the team members also studied the factors affecting the structural, mechanical, and magnetic properties of metal Fe [ 47 , 48 ], Al [ 49–51 ], Ni [ 52–54 ], Ag [ 55 ], alloys AlNi [ 56 ], NiCu [ 57 , 58 ], FeNi [ 59 , 60 ], AgAu [ 61 ], NiAu [ 62 ], and replace the H derivatives of poly C 13 H 8 OS-H with metal atoms Br, Cu, Kr, Ge, As, Fe [ 63 ] showed that the E g band gap decreased, leading to an increase in the conductivity. The obtained results will contribute to research to find materials new for application in the industrial age.…”
Section: Introductionmentioning
confidence: 99%